The MaMBA-concept for an extraterrestrial base and its first module mock-up. (August 2020) - Heinicke, C.; Orzechowski, L.; Avila, M.
Abstract: Habitats must enable astronauts to survive in an extraterrestrial environment, but the challenge is not only a technological one: architecture and engineering should be brought together to create an environment in which a crew can perform optimally. With missions to Mars in mind, crew mental health becomes a design driver equally important to the support of physiological functions. We here suggest a habitat concept, MaMBA (short for Moon and Mars Base Analog), which combines the two requirements. In its basic configuration, MaMBA consists of six upright cylindrical, hard-shell pressure vessels as main modules and two airlocks, which are all connected with inflatable corridor modules. We present the current state of the design and particularly focus on the laboratory module, of which we have constructed a mock-up equipped with scientific instrumentation. In the long-term, we plan to develop this laboratory module into a functional prototype including subsystems such as the life support system. Eventually, we aim to create a habitat which can serve as a test platform (for technologies, operations, and procedures) and whose usability is continually validated through iterative testing with human inhabitants. The habitat is open to international partners for simulations.